Polaprezinc for prevention of oral mucositis in patients receiving chemotherapy followed by hematopoietic stem cell transplantation: A multi‐institutional randomized controlled trial. Issue 6 (14th October 2020) - Kitagawa, Junichi; Kobayashi, Ryo; Nagata, Yasuyuki; Kasahara, Senji; Ono, Takaaki; Sawada, Michio; Ohata, Koichi; Kato‐Hayashi, Hiroko; Hayashi, Hideki; Shimizu, Masahito; Itoh, Yoshinori; Tsurumi, Hisashi; et al.
Abstract: Oral mucositis is a common and distressing complication in patients receiving high‐dose chemotherapy followed by hematopoietic stem cell transplantation (HSCT). We reported previously in a single‐center retrospective analysis that zinc‐L‐carnosine (polaprezinc [PZ]) reduced the incidence of oral mucositis associated with HSCT. To verify the accuracy of the prophylactic effect of PZ against oral mucositis, we carried out a multi‐institutional prospective randomized controlled study. Patients were randomly allocated to either the prevention group, in which PZ lozenge treatment was started before chemotherapy, or the control group, in which administration of PZ lozenges was initiated immediately after the onset of Grade 2 oral mucositis. Oral mucositis was evaluated daily from the start of chemotherapy to 35 days after transplantation. A total of 91 patients were enrolled, and 88 patients (47 in the control group and 41 in the prevention group) were eligible for data analysis. The incidence of Grade ≥2 but not Grade ≥3 oral mucositis was significantly reduced in the prevention group compared to the control group (44.7% in control group vs 22.0% in the prevention group, P = .025). There were no significant differences in the incidence rates of other adverse events or the rate of engraftment (95.6% vs 97.2%, P = .693) between the two groups. These findings suggest that PZ lozenge is effective for prophylaxis against Grade ≥2 oral mucositis associated with chemotherapy in patients undergoing HSCT without any influence on the HSCT outcome. What's new?: Chemotherapy‐induced oral mucositis is a common, painful condition that can result in an inability to eat, affecting patient nutrition. In this multi‐institutional randomized controlled study, the authors investigated the ability of polaprezinc (PZ) lozenges to prevent oral mucositis associated with conditioning chemotherapy in patients undergoing hematopoietic stem cell transplantation (HSCT). PZ lozenges effectively prevented grade ≥2 oral mucositis associated with chemotherapy in about 22 percent of HSCT patients, with no impact on HSCT outcome. The lozenges did not prevent grade ≥3 mucositis. The findings indicate that PZ lozenges are effective against moderate oral mucositis in some patients.